Iron house [large type] - Hart, John, 1965- (Thorndike Press large print core, 2011)
There was nothing but time at Iron House. Time to burn, time to kill, and time for Michael to emerge strong and unforgiving while his brother, Julian, became a tormented soul at the orphanage for boys. Two decades later Michael returns to North Carolina with a sentence on his head, the mob in hot pursuit, and his disturbed brother in trouble of a different kind. One man is destined to break the chains of his fate.